The Influence of Work Motivation, Leadership, and Career Development on Employee Performance at the Human Resources Development Center for Air Transportation, Curug Tangerang - Zaman Zaini; Lilis Kurnianingsih (IJESS International Journal of Education and Social Science, 2022)
This study aims to analyze and evaluate the influence of work motivation leadership, and career development on employee performance. This research method used a quantitative approach. The population of this study was all employees at the Human Resource Development Center of Air Transportation in CurugTangerang and they were 70 people in total. The research sample was 69 people (saturation sampling). Based on the research results, it shows that work motivation has a positive and significant effect on employee performance by 12,4%, leadership has a positive and significant effect on employee performance by 51.5%,career development has a positive and significant effect on employee performance by 27.4% and work motivation, leadership and on career development have a positive and significant effect on employee performance at the Human Resource Development Center of Air Transportation in Curug Tangerang by 90.9% and the remaining 9.1% is the contribution of other variables outside this study.